Correction of T cell deficiency in ZAP‐70 knock‐out mice by simple intraperitoneal adoptive transfer of thymocytes. (12th March 2018) - Kugyelka, R.; Kohl, Z.; Olasz, K.; Prenek, L.; Berki, T.; Balogh, P.; Boldizsár, F.
Summary: The tyrosine kinase zeta chain‐associated protein of 70 kDa (ZAP‐70) plays a key role in T cell development and signalling. In the absence of ZAP‐70, T cell development is arrested in the CD4 + CD8 + double‐positive stage, thus ZAP‐70 homozygous knockout (ZAP‐70 –/– ) mice have no mature T cells in their peripheral lymphoid organs and blood, causing severe immunodeficiency. We investigated the early kinetics and long‐term effects of wild‐type thymocyte transfer on T cell repopulation in ZAP‐70 –/– mice. We used a single intraperitoneal (i.p.) injection to deliver donor thymocytes to the recipients. Here, we show that after i.p. injection donor thymocytes leave the peritoneum through milky spots in the omentum and home to the thymus, where donor‐originated CD4 – CD8 – double‐negative thymocytes most probably restore T cell development and the disrupted thymic architecture. Subsequently, newly developed, donor‐originated, single‐positive αβ T cells appear in peripheral lymphoid organs, where they form organized T cell zones. The established chimerism was found to be stable, as donor‐originated cells were present in transferred ZAP‐70 –/– mice as late as 8 months after i.p. injection. We demonstrate that a simple i.p. injection of ZAP‐70 +/+ thymocytes is a feasible method for the long‐term reconstitution of T cell development in ZAP‐70‐deficient mice. Abstract : In the absence of ZAP‐70 kinase, T cell development is arrested in the CD4+CD8+ double positive stage, thus ZAP‐70 homozygous knockout (ZAP‐70‐/‐) mice have no mature T cells in their peripheral lymphoid organs and blood, causing severe immunodeficiency. Here, we demonstrate that a simple, intraperitoneal injection of ZAP‐70+/+ thymocytes is a feasible method for the long‐term reconstitution of T cell development in ZAP‐70 deficient mice.